PRODUKTIVITAS SELAMA WORK FROM HOME: SEBUAH ANALISIS PSIKOLOGI SOSIAL - Agung Minto Wahyu; Mochammad Sa'id (Jurnal Kependudukan Indonesia, 2020)
The spread of the COVID-19 pandemic requires each country to limit activities of its people outside the home by doing Work from Home (WFH). The purpose of this paper is to reveal the impact of WFH on worker productivity in the perspective of social psychology. The analysis shows that during WFH, worker productivity can increase due to the effects of social facilitation. Workers perceive the presence of others as triggers to increase their productivity. Conversely, workers' productivity can also decrease during working together with others because the presence of other people is perceived as a threat. On the other hand, job demands, distractors, and facilitators can activate the latent personality trait of an individual so that it manifests into a new work behavior during WFH. Strategies to maintain productivity is to use brainstorming, break down work teams into smaller, as well as the application of Nominal Group Technique